Media Exposure Related to the PTSS During COVID-19 Pandemic: The Mediating Role of Risk Perception - Wang, Yiqing; Jiang, Ling; Ma, Shuang; Chen, Qinian; Liu, Chengbin; Ahmed, Farooq; Shahid, Muhammad; Wang, Xiaohua; Guo, Jing (Frontiers in Psychiatry, 2021)
Objectives: The objectives of this study are to assess the relationship between media exposure and posttraumatic stress symptoms (PTSS) and to highlight the underlying mechanisms mediated by risk perception. Methods: This survey was conducted online in China from February 1st to February 10th, 2020. A total of 2858 Chinese citizens aged ≥18 years from 31 provinces and autonomous regions were recruited to participate in a cross-sectional study. Self-report questionnaires were used to assess media exposure, PTSS, and risk perception. Results: The prevalence of respondents with heightened PTSS scores was 22.2%. After controlling for covariates, media exposure (more than 5 times a day) was significantly and positively associated with a high level of PTSS (B=4.11, p<0.001), and risk perception (worry and severity) significantly mediated the relationship between media exposure and PTSS (all 95% CIs did not include 0). Conclusions: Based on these findings, the frequency of media exposure was associated with PTSS. Risk perception (worry and severity) mediated the relationship between media exposure and PTSS. The mental health, particularly PTSS, of the general population should be closely monitored and “infodemics” should be combatted while addressing the COVID-19 outbreak; cognitive interventions may be promising.